1995
DOI: 10.1111/j.1440-1681.1995.tb01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine a Hepatotoxicity: Effect of Prolonged Treatment With Cyclosporine on Biliary Lipid Secretion in the Rat

Abstract: 1. The effects of cyclosporine A (CyA) treatment on liver morphology, bile flow and biliary secretion of bile acid, cholesterol and phospholipid and some plasma biochemical indicators of liver function were examined. 2. Wistar rats were treated i.p. with 10 or 20 mg of CyA/kg per day for 1, 2, 3 or 4 weeks. 3. Treatment increased bile acid and bilirubin plasma concentration. Bile flow and biliary secretion of bile acid, cholesterol and phospholipid were reduced in CyA-treated animals. 4. All these effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…Although no remarkable histological changes were observed in the cyclosporine A-treated group (table 4), functional impairment of cells in the biliary canaliculi appeared to be induced, as suggested by the increase in serum total bilirubin and total bile acids with cyclosporine A at both 10 and 20 mg/kg. There have also been reports that administration of cyclosporine A at the same doses resulted in significant decrease in bile flow and bile acid secretion [14][15][16]. Therefore, cyclosporine A was considered to have produced cholestasis as with 4,4¢-methylene dianiline, a-naphthylisothiocyanate and bile duct ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no remarkable histological changes were observed in the cyclosporine A-treated group (table 4), functional impairment of cells in the biliary canaliculi appeared to be induced, as suggested by the increase in serum total bilirubin and total bile acids with cyclosporine A at both 10 and 20 mg/kg. There have also been reports that administration of cyclosporine A at the same doses resulted in significant decrease in bile flow and bile acid secretion [14][15][16]. Therefore, cyclosporine A was considered to have produced cholestasis as with 4,4¢-methylene dianiline, a-naphthylisothiocyanate and bile duct ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Three groups of animals received repeated intraperitoneal administration of cyclosporine A (10 or 20 mg/kg/day for 14 days, n ¼ 5) or vehicle (saline solution, n ¼ 5) as control-2. The dose and period of administration of cyclosporine A were selected based on previous studies [14][15][16]. Other groups of rats received a single oral administration of 4,4¢-methylene dianiline (75 mg/kg, n ¼ 5), a-naphthylisothiocyanate (75 mg/kg, n ¼ 5) or vehicle (0.5% methylcellulose solution, n ¼ 5) as control-3.…”
Section: Methodsmentioning
confidence: 99%
“…3 Bile flow and secretion of bile acid, cholesterol, and phospholipids are reduced during CsA treatment. 4,17 In the liver, most of the blood flow enters through the portal vein, and the resistance changes are thought to occur in the microvascular anastomosis of the portal and hepatic veins, known as hepatic sinusoids. Shah et al 19 have recently reported that in rat liver, eNOS is abundantly expressed in the sinusoidal endothelial cells and that these cells respond to shear stress by increasing NO release.…”
Section: Sánchez-lozada Et Al Nos Mrna Expression In Csa Toxicity 645mentioning
confidence: 99%
“…3,4 In isolated perfused rat liver, CsA administration produced a dose-dependent reduction of bile flow, increased the release of cytosolic and mitochondrial enzymes, and decreased oxygen consumption. 3 High blood levels of CsA in human allograft recipients have been associated with an increase in ␥-glutamyl transpeptidase, a liver enzyme that correlates with hepatotoxicity.…”
mentioning
confidence: 99%
“…Its ATP-dependent excretion to the bile via Mrp2 is an important driving force for bile acid-independent bile flow. Rats treated with cyclosporine A have reduced GSH secretion into bile and bile acid-independent bile flow (Moran et al 1998), conjugated hyperbilirubinemia (Galan et al 1995), and increased lipid peroxidation (Galan et al 1999). In our study, both GCSlc and GCShc mRNA were down-regulated after cyclosporine A.…”
Section: Gsh Metabolising Enzymes and Mrp2mentioning
confidence: 99%